Formação e atividade docente na educação infantil em articulação ao currículo: narrativas com possibilidades de transformação - Frenham, Adriana Maria Biaggio (2023)
The movement of reality has always impacted educational policies, so we would like to highlight the look at the Early Childhood Education Stage Pre-School, through this research - in rhizomatic configuration -, considering aspects related to professional experiences of teaching, curricular aspects of Childhood and, consequently, possible impacts and developments in the contexts of permanent formation that occurred in the school environment. To this end, the problem was listed "how the historical, political-curricular, theoretical, practical and contextual movements impact and unfold in the activity and training of [a group of] Early Childhood Education teachers, with classes of 4 and 5 years old”? As a result, the objectives were outlined: to problematize the historical, political-curricular, theoretical, practical and contextual movements aimed at the Early Childhood Education stage; discuss how such milestones had repercussions on the training of teaching subjects working in that stage; apprehend, from professional narratives, what would be the possible impacts and developments in the activity and in the formative contexts experienced by preschool teachers and coordinators, considering the cited movements; and, to reflect on the main resignifications of knowledge and practices in Early Childhood Education (4 and 5 years old) from such apprehended impacts and developments.Accordingly, a qualitative research was chosen, with a narrative approach, considering that the data collection took place through semi-structured interviews, involving teachers and pedagogical coordinators working in Early Childhood Education, in a Municipal Public Network education. The data were approached through Content Analysis, comprising for the interpretation of the set of meanings present in the narratives of the professionals participating in the research, three categories, namely: I – Professional Experiences; II – Curriculum, Children and School; and, III – Professional Training. Each of these groupings had Axes of Analysis that, integrated with each other, led to the following items: a possible impact present in the Early Childhood Educacion Institutions, both in the scope of pedagogical work and in the curriculum, comes from the attempt to overcome a history of welfare, preparatory and children, subject to social, economic and political issues; another possible impact is found in the processes experienced during the pandemic and post-pandemic period, which generated an important movement of reflection, of re-signification of pedagogical and curricular practices, as well as training paths; as a development, the growing movement of transposition of these same pedagogical conceptions was evident, mainly in relation to the potency of children, as well as the transformation of practices aimed at curricular movements committed to these same children in their entirety